PERSEPSI GURU PAUD TENTANG PENTINGNYA PELATIHAN KURIKULUM MERDEKA - Chairun Nisa Fadillah; Munawarah Munawarah; Reza Aulia (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
For curriculum development and classroom implementation to be successful, teachers must be fully supported. The process of developing and implementing the curriculum is very dependent on the teacher, for this reason all teachers must receive ongoing training in order to increase their professionalism and understanding of the applicable curriculum. In this study, an interactive qualitative data analysis model was used which was adopted from a qualitative descriptive research method where the researcher collected data repeatedly so that the results obtained were more accurate. This research was conducted in one of the private PAUD schools in the Aceh Tamiang area with the subject being teachers who had attended independent learning training. The findings obtained from this research are that teachers are very enthusiastic to be able to understand the concepts in the independent curriculum so that they can apply them in classroom learning. Teachers feel very responsible for implementing this independent curriculum in the learning process because teachers play a very important role in the development and implementation of the curriculum in schools. Based on this research, it can be concluded that the independent curriculum makes students more free to learn and develop themselves. The independent curriculum is also more interactive, providing opportunities for students to explore their insights. Therefore the teacher becomes a vital facilitator in exploring, overseeing and leading the development of students' skills. Independent curriculum training is the main medium for aligning perceptions regarding the principles and objectives of implementing the curriculum, so that a truly independent learning climate will be created and students will have strong resilience in studying or constructing problem solving